20*(20+x)=15*(15+3x)

Simple and best practice solution for 20*(20+x)=15*(15+3x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 20*(20+x)=15*(15+3x) equation:


Simplifying
20(20 + x) = 15(15 + 3x)
(20 * 20 + x * 20) = 15(15 + 3x)
(400 + 20x) = 15(15 + 3x)
400 + 20x = (15 * 15 + 3x * 15)
400 + 20x = (225 + 45x)

Solving
400 + 20x = 225 + 45x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-45x' to each side of the equation.
400 + 20x + -45x = 225 + 45x + -45x

Combine like terms: 20x + -45x = -25x
400 + -25x = 225 + 45x + -45x

Combine like terms: 45x + -45x = 0
400 + -25x = 225 + 0
400 + -25x = 225

Add '-400' to each side of the equation.
400 + -400 + -25x = 225 + -400

Combine like terms: 400 + -400 = 0
0 + -25x = 225 + -400
-25x = 225 + -400

Combine like terms: 225 + -400 = -175
-25x = -175

Divide each side by '-25'.
x = 7

Simplifying
x = 7

See similar equations:

| 6+17(-10-8g)= | | 2q-5=7q | | 75+2=15+5 | | 11-3x+6y=0 | | P(n)=3n | | 10a-7(-17a-13)= | | (x*x)=(x-2)*(x+2) | | 21+5=15+11 | | X*12=6*(x+4) | | y=-0.2*36+50 | | 2x+53+68=75 | | k/5-9=-17 | | (x-y+2)-(x+7-2y)= | | s=250+12y | | (x*x)=x-2*x+2 | | y=2*3+2 | | x^3+12x=8x^2 | | tan7=140/x | | 8=f/4 | | 33=s-13 | | x-(x*.25)=84000 | | 4(2x-1)+3x=11 | | 6*(6+x)=5*17 | | 7x^2+42x+7y^2-70y=105 | | 16=t/13 | | 5x-3-2=3x-5+7x | | 150+30n=420 | | 5+7n=9n+1 | | 32-80d-87-3d+9+8d= | | (15*15)=9*(9+4x) | | 5w+15=3w-5 | | -4x^2-12x=-5 |

Equations solver categories